2013
DOI: 10.1016/j.amepre.2013.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourced Peer- Versus Expert-Written Smoking-Cessation Messages

Abstract: Background Tailored, web-assisted interventions can reach many smokers. Content from other smokers (peers) through crowdsourcing could enhance relevance. Purpose To evaluate whether peers can generate tailored messages encouraging other smokers to use a web-assisted tobacco intervention (Decide2Quit.org). Methods Phase 1: In 2009, smokers wrote messages in response to scenarios for peer advice. These smoker-to-smoker (S2S) messages were coded to identify themes. Phase 2: resulting S2S messages, and compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 34 publications
1
48
0
Order By: Relevance
“…The messaging database included 261 messages that were developed in our previous RCT and included both expert-written messages and peer-written messages [17]. Messages written by experts (study designers, behaviorists, physicians, nurses) were developed through an iterative expert group review process.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The messaging database included 261 messages that were developed in our previous RCT and included both expert-written messages and peer-written messages [17]. Messages written by experts (study designers, behaviorists, physicians, nurses) were developed through an iterative expert group review process.…”
Section: Methodsmentioning
confidence: 99%
“…The current guidelines provided evidence-based content on successful cessation strategies. The SCT, which incorporates vicarious learning and verbal persuasion, informed the content of the expert messages [17]. Messages reflected theoretical determinants of quitting, such as positive outcome expectations and self-efficacy enhancing small goals [19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Social influences play an important role in quitting smoking among individuals without mental illness (Cohen & Lichtenstein, 1990;Gulliver, Hughes, Solomon, & Dey, 1995;Yang et al, 2013), and some smoking cessation interventions have leveraged social support in the cessation process with promising results (Coley et al, 2013;Hennrikus et al, 2010;Stewart et al, 2010). To better understand social influences on smoking cessation and how they may be incorporated into treatment models, prior research in the general population has distinguished between explicit and implicit social influences on smoking cessation (van den Putte, Yzer, & Brunsting, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Individuals can now interact with, shape, and even disseminate their own intervention messages through their social networks by using features, such as comments, likes, shares, and tweets. However, it is critically important that programs delivered via such platforms are designed and delivered with an understanding of the user experience and how individuals will respond to, shape, and share such content and programs (25,29). For example, a recent study revealed that positive and derisive viewer comments shaped other users' evaluations of the credibility of antimarijuana health messages delivered via YouTube (127).…”
mentioning
confidence: 99%